Open access week 2021 at the University of Eastern Finland Library: How we designed, marketed, and conducted workshop, Cafés, prizes, and postings - Ovaska, Tuulevi (Journal of EAHIL, 2022)
International Open Access Week is a global event that many institutions and organisations take part in annually. Often the libraries of academic institutions are eager to participate. The level of participation can vary from simply sharing knowledge about the week to, for example, organising events. In 2021, the University of Eastern Finland library decided to put more effort to the week than before, since it has a role as an active promoter of open science. Medical Subject Headings: Anniversaries and Special Events; Awards and Prizes; Blogging; Libraries; Open Access Publishing